Diagnostic approaches to acute transfusion reactions - Leo, Albrecht; Pedal, Ingo (Forensic science, medicine, and pathology, 2010)
The erroneous transfusion of ABO-incompatible red cells may lead to life-threatening hemolysis and complement-induced shock, resulting in death in less than 10% of cases (acute hemolytic transfusion reaction, AHTR). Identification of the cause of an erroneous transfusion is accomplished in nearly all incidents merely by checking the identity of the patient, blood sample and blood bag. The erroneous transfusion is confirmed by serological and—in the case of a fatality- immunohistochemical methods. The differential diagnosis should rule out transfusion-related acute lung injury (TRALI), other immunologically triggered causes such as febrile nonhemolytic transfusion reaction (FNHTR) or allergic reactions, but also nonimmunological causes such as bacterial contamination of the blood components, transfusion-associated circulatory overload (TACO) and other rare events such as citrate overload or embolism (by air or debris). In the case of a fatality, evaluation of a patient′s medical records, serological and microbiological analyses, autopsy and histology, taken together, clarify questions of causality.